Foreign Trade of the Republic of Belarus in the International Business Environment - Hrechyshkina Olena; Samakhavets Maryia (Bulletin of Geography. Socio-Economic Series)
The aim of the paper is to assess the current state, problems and prospects for the development of foreign trade in the Republic of Belarus in the international business environment. The evaluation of foreign trade indicators is based on information from different sources and on comparative economic analysis research methods. Our results indicate the export-oriented economy of the Republic of Belarus, and its dependence on the state of foreign markets and the international business environment. The identified problems in the development of Belarusian merchandise exports are due to the orientation towards primary products, and to poor diversification of products and geographical destination. Particular attention is paid to the internal and external factors restraining exports from the Republic of Belarus. Further development requires the full use of the Belarusian export potential and the implementation of measures to promptly resolve the export difficulties on international markets that stem from internal and external factors.